Recombinant Adeno-Associated Viral Vectors Expressing Human Coagulation FIX-E456H Variant in Hemophilia B Mice - Le Quellec, Sandra; Dane, Allison P.; Barbon, Elena; Bordet, Jean-Claude; Mingozzi, Federico; Dargaud, Yesim; Marais, Thibaut; Biferi, Maria-Grazia; Négrier, Claude; Nathawani, Amit C.; Enjolras, Nathalie (Thrombosis and Haemostasis, 2019)
Gene therapy using recombinant adeno-associated virus (AAV) has induced sustained long-term coagulation human factor IX (hFIX) levels in hemophilia B (HB) patients. However, asymptomatic transient liver toxicity was observed at high vector doses, highlighting the need to improve the potency of these vectors. We report the generation of an AAV transgene cassette containing the hyperfunctional hFIX-E456H variant showing improved binding to platelets, with a comparison to wild-type hFIX (hFIX-WT) and hFIX-R384L variant (Padua) transgenes, containing F9 truncated-intron 1 (I1). In vitro specific activity was increased by 3.2- and 4.2-fold with hFIX-E456H and hFIX-R384L variants compared with hFIX-WT, using chromogenic assay, and by 7-and 8.6-fold with hFIX-E456H and hFIX-R384L variants compared with hFIX-WT, using one-stage assay. The transgenes were packaged into single-stranded AAV2/8 vectors that were tail vein injected at 5 × 109, 2 × 1010, and 5 × 1010 vg per mouse in HB mice. Plasma FIX activity level, assessed by chromogenic assay, was up to fourfold higher for hFIX-E456H compared with hFIX-WT and was not different compared with hFIX-R384L, among the three dose cohorts. Overall, the in vivo specific activity was increased by threefold for hFIX-E456H and 4.9-fold for hFIX-R384L compared with hFIX-WT. At the lower dose of 5 × 109 vg, the blood loss was significantly lower for hFIX-E456H compared with hFIX-WT, but did not differ compared with hFIX-R384L. The results found for the hFIX-E456H variant indicate that it might be a suitable alternative for gene therapy of HB.
Keywords: gene therapy; hemophilia B; factor IX; platelets; factor IX Padua